Academic Quality Dimensions and its influence on Students’ Satisfaction - Cruz Macedo, Maria Erilucia (International Journal of Humanities and Education Development (IJHED), 2022)
Today in many industries service quality is widely used in different sectors. Every sector whether services sector or manufacturing can apply and implement five dimensions of service quality. The purpose of this study is to reveal the impact of service quality on student’s satisfaction in education sectors. The findings of the study will show impact of different service quality dimensions on students’ satisfaction in a private university. This study is useful to see the significance of service quality to satisfy students. SERVQUAL model of service quality provided by (Parasuraman, et al., 1988) is implemented. It includes five dimensions tangible, reliability, responsiveness, assurance and empathy. Findings of this study showed that four of service quality dimensions (tangible, responsiveness, assurance and empathy) have positive association with student satisfaction, except reliability have negative association with student satisfaction.